Up-Regulated Expression of Interferon-Gamma, Interleukin-6 and Tumor Necrosis Factor-Alpha in the Endolymphatic Sac of Meniere's Disease Suggesting the Local Inflammatory Response Underlies the Mechanism of This Disease - Huang, Chao; Wang, Qin; Pan, Xueying; Li, Wei; Liu, Wei; Jiang, Wenqi; Huang, Li; Peng, Anquan; Zhang, Zhiwen (Frontiers in Neurology, 2022)
Background Immune mediated inflammatory changes affecting the endolymphatic sac (ES) may underlie the pathology of Meniere’s disease (MD). The aim of the present study was to explore the differentially expressed cytokines in ES luminal fluid (ELF) of patients with MD, and the correlation between the expression of cytokines in the ELF with that in the serum was determined by quantitatively analyzing the cytokines in human ELF and serum. Methods Human ELF, serum and ES tissues were collected from patients with unilateral MD and patients with acoustic neuroma (AN) during surgery. The Simoa Cytokine 6-Plex Panel kit was used to analyze the levels of cytokines in the ELF and blood samples of the patients. Immunohistochemistry and immunofluorescence were subsequently used to validate the relative expression levels of the cytokines in MD. Results Significant differences were identified in the expression levels of interferon-γ (IFN-γ) (P<0.001), interleukin (IL)-6 (P=0.008) and tumour necrosis factor-α (TNF-α) (P=0.036) in the luminal fluid of the ES comparing between the MD and AN groups. By contrast, the levels of IFN-γ, IL-10, IL-12p70, IL-17A, IL-6 and TNF-α in the serum of the MD group were not significantly different from those of either the AN group or healthy control subjects. In addition, no significant correlations in the expression levels of cytokines compared between the ELF and serum were found for the patients in either the MD or the AN group. Finally, the detection of positive expression of TNF-α, IL-6 and IFN-γ in the epithelial cells of the majority of ES specimens from patients with MD confirmed the up-regulated expression of these cytokines in the ES of patients with MD. Conclusions The identification of up-regulated expression levels of TNF-α, IL-6 and IFN-γ in the ELF in the present study has provided direct evidence for an increased immunologic activity in the microenvironment of the ES in patients with unilateral MD, may suggest the local inflammatory response underlies the mechanism of this disease.